Reformulasi ijtihad dalam pembaruan hukum Islam menuju hukum nasional: Ikhtiar metodologis A. Qadri Azizy mentransformasikan fikih Timur Tengah ke Indonesia - Warkum Sumitro; Fiqh Vredian Aulia Ali (State Institute of Islamic Studies (IAIN) Salatiga, 2015)
This study is an elaboration of creative minds of A. Qodry Azizy about reformulation of ijtihad thatwas developed through reformation of “ mazhab” and an eclecticism of national law. Researchers useda qualitative research with a research library approach through technical documentation. An offering ofreformulation of ijtihad of A. Qodri Azizy motivated by social and academical anxiety about theentity of life after reformation and the probability of social changes with the momentum of GBHN1999.Therefore, it is neccesarily a Guidelines about formulations on” fiqh” which is suitable by the contextof Indonesian. He started on the concerns of intention, an inner attitude and academical confidence inapplication of Islamic law through the agenda of reformation on “mazhab” and positivization ofIslamic law within the framework of development of national laws.